2018
DOI: 10.1177/0003702818792289
|View full text |Cite
|
Sign up to set email alerts
|

Deep Ultraviolet Standoff Photoacoustic Spectroscopy of Trace Explosives

Abstract: We demonstrate deep ultraviolet (UV) photoacoustic spectroscopy (PAS) of trace explosives using a sensitive microphone at meter standoff distances. We directly detect 10 µg/cm of pentaerythritol tetranitrate (PETN), 2,4,6-trinitrotoluene (TNT), and ammonium nitrate (AN) with 1 s accumulations from a 3 m standoff distance. Large PAS signals for standoff detection are achieved by exciting into the absorption bands of the explosives with a 213 nm laser. We also investigate the impact of the deep UV photochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Sensitivities of 5 and 10 µg/cm 2 of the hazardous chemicals, such as acetic acid, PETN (pentaerythritol tetranitrate), and DPA (dipicolinic acid), are achieved with frequencies of 25 and 42 kHz, respectively, at a distance of 0.5 m. The technique has great potential for screening of suspicious objects for security check and forensic applications. Noting that many explosives have strong absorption at deep ultraviolet (UV) band [148], Alyssa B. Zrimsek et al have demonstrated deep UV PAS of trace explosives using a sensitive microphone at meter standoff distances [149]. Different from most studies using QCLs as laser sources, they directly detect 10 µg/cm 2 of pentaerythritol tetranitrate (PETN), 2,4,6-trinitrotoluene (TNT), and ammonium nitrate (AN) by using a 213 nm laser with 1 s accumulations from a 3 m standoff distance.…”
Section: Standoff Lpas With Microphonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivities of 5 and 10 µg/cm 2 of the hazardous chemicals, such as acetic acid, PETN (pentaerythritol tetranitrate), and DPA (dipicolinic acid), are achieved with frequencies of 25 and 42 kHz, respectively, at a distance of 0.5 m. The technique has great potential for screening of suspicious objects for security check and forensic applications. Noting that many explosives have strong absorption at deep ultraviolet (UV) band [148], Alyssa B. Zrimsek et al have demonstrated deep UV PAS of trace explosives using a sensitive microphone at meter standoff distances [149]. Different from most studies using QCLs as laser sources, they directly detect 10 µg/cm 2 of pentaerythritol tetranitrate (PETN), 2,4,6-trinitrotoluene (TNT), and ammonium nitrate (AN) by using a 213 nm laser with 1 s accumulations from a 3 m standoff distance.…”
Section: Standoff Lpas With Microphonesmentioning
confidence: 99%
“…Noting that many explosives have strong absorption at deep ultraviolet (UV) band [148], Alyssa B. Zrimsek et al have demonstrated deep UV PAS of trace explosives using a sensitive microphone at meter standoff distances [149]. Different from most studies using QCLs as laser sources, they directly detect 10 µg/cm 2 of pentaerythritol tetranitrate (PETN), 2,4,6-trinitrotoluene (TNT), and ammonium nitrate (AN) by using a 213 nm laser with 1 s accumulations from a 3 m standoff distance.…”
Section: Standoff Lpas With Microphonesmentioning
confidence: 99%
“…[15] Tunable laser repetition rates are desirable for many spectral techniques such as standoff photoacoustic spectroscopy. [28] Our second-generation 228-nm laser was miniaturized and optimized to achieve maximum output powers.…”
Section: -Nm Laser Designsmentioning
confidence: 99%
“…[ 15 ] Tunable laser repetition rates are desirable for many spectral techniques such as standoff photoacoustic spectroscopy. [ 28 ]…”
Section: Development Of New 228‐nm Lasermentioning
confidence: 99%
“…The photoacoustic methodology, in general, using mid-IR wavelength and microphone detector has been discussed by many researchers [10][11][12][13][14][15][16] . Zrimsek et al have demonstrated standoff photoacoustic spectroscopy of trace explosives from a meter distance using a sensitive microphone and 213 nm laser 17 . In their research, they found that the formation of gaseous species due to the photochemistry of explosives enhances the photoacoustic signal strength but at the same time reduces the lifetime of the signal in case of detection in trace quantity of analytes.…”
mentioning
confidence: 99%